Program Psikoedukasi Sebagai Upaya Pencegahan Perilaku Bullying Pada Siswa Madrasah Aliyah Arifah Gowa - Ahmad Yasser Mansyur; Ahmad Razak; Uldiyanti Sya'diah Syahdan; Ainul Bahri; A. Muh Raafi Dwi Zaldi (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Cases of bullying are currently quite widespread in the school environment. Cases of bullying have a huge impact on the mental health of students. One way that can be done to reduce the level of bullying cases is to do psychoeducation. The purpose of this research is to prevent bullying behavior by conducting psychoeducation to students. The research method used in this research is psychoeducation. The analysis technique uses a qualitative descriptive method. Based on the research that has been done, the results obtained are that students can conclude well the material presented and give a good impression and positive insight. Students are also able to understand the importance of preventing bullying behavior.